Pengaruh Pemberian Beban terhadap Kekuatan M. Antebrachii pada Mahasiswa Kedokteran - Ridha, Sania Maulidia Ar; Kumala , Noer; Soekanto, Ayly; Herliani, Olivia (Calvaria Medical Journal, 2026)
Background: Muscle strength plays an important role in supporting daily activities involving the M. antebrachii, such as gripping, lifting, and writing. Medical students often have demanding academic schedules that limit their physical activity, potentially affecting muscle strength. Although resistance training has been shown to improve muscle strength through neuromuscular adaptations, evidence regarding the effectiveness of short-term resistance training on M. antebrachii strength in medical students remains limited. Objective: To analyze the effect of resistance training on M. antebrachii muscle strength among medical students. Methods: This study employed a pre-experimental design with a one-group pretest–posttest approach. Muscle strength was measured before and after the intervention using a handgrip dynamometer. Data were analyzed using a paired-samples t-test to compare the mean muscle strength before and after the intervention. Cohen’s d effect size was also calculated to determine the magnitude of the intervention effect. Results: The mean muscle strength increased by 0.31 kg after the resistance training intervention compared with the baseline measurement. However, the paired-samples t-test showed no statistically significant difference between pretest and posttest results (p = 0.680; p > 0.05). Furthermore, the effect size analysis yielded a Cohen’s d ≤ 0.075, indicating a trivial effect. Conclusion: Short-term resistance training did not produce a statistically significant improvement in M. antebrachii muscle strength among medical students. Although there was a slight increase in the mean muscle strength, the change was minimal and not statistically significant. This finding may be associated with the short duration of the intervention and the fact that the participants were fasting during the study period.